2020
DOI: 10.3390/biomedicines9010022
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitin Ligase SIAH2 Negatively Regulates Glucocorticoid Receptor Activity and Abundance

Abstract: Glucocorticoids are clinically essential drugs used routinely to control inflammation. However, a host of metabolic side effects manifests upon usage beyond a few days. In the present study, we tested the hypothesis that seven-in-absentia mammalian homolog-2 (SIAH2), a ubiquitin ligase that regulates adipogenesis, is important for controlling adipocyte size, inflammation, and the ability of adipose tissue to expand in response to a glucocorticoid challenge. Using mice with global deletion of SIAH2 exposed or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Lastly, a recent study by Burke et al [141] identified the E3 ligase, seven-in-absentiamammalian homolog-2 (Siah2) as a modulator of GRα protein levels. Siah2 is a known regulator of fat mass and inflammation within adipose tissue [159,160] and has been shown to lead to the agonist-dependent activation of steroid receptors, such as GRα [156].…”
Section: Ups Enzymes That Modulate Grα Protein Levelsmentioning
confidence: 99%
“…Lastly, a recent study by Burke et al [141] identified the E3 ligase, seven-in-absentiamammalian homolog-2 (Siah2) as a modulator of GRα protein levels. Siah2 is a known regulator of fat mass and inflammation within adipose tissue [159,160] and has been shown to lead to the agonist-dependent activation of steroid receptors, such as GRα [156].…”
Section: Ups Enzymes That Modulate Grα Protein Levelsmentioning
confidence: 99%